The impact of digital technology on total factor productivity in manufacturing enterprises - Jian Tu; Xin Wei; Muhammad Ashlyzan Bin Razik (Scientific Reports)
Abstract Digital technology drives high-quality development in manufacturing while serving as a critical enabler for advancing the digital economy. Using data from the Chinese list of manufacturing enterprises from 2012 to 2023, this study empirically analyzes the impact of digital technology on total factor productivity (TFP) in manufacturing and its mechanism of action and further explores its heterogeneity. The results show that digital technology has significantly promoted total factor productivity in manufacturing; this effect was still valid after a series of robustness tests and endogeneity tests were conducted. The mechanism analysis indicated that digital technology enhances total factor productivity in the manufacturing enterprises through the enhancement of the innovation ability of enterprises and the reduction in the operation and management costs. The heterogeneity analysis showed that digital technology has a more significant effect on the total factor productivity enhancement of enterprises in the eastern region, state-owned enterprises, and small and medium-sized enterprises. The conclusions provide clear policy implications for the promotion of the digital transformation of enterprises, accelerating the formation of high-quality productivity in enterprises, and promoting the high-quality development of the manufacturing industry.